Innovation of the Moringa Oleifera Formula for Stunting Prevention in Toddlers - Usman Usman; Ruslang T; Herlina Rantedatu; Megawati Megawati; Fatmawati Yusuf (Sarana Ilmu Indonesia (salnesia), 2023)
The problem of stunting still threatens Indonesia, especially in toddlers. Innovations that can be applied to toddlers are brownies and roll cakes. The aim of the study was to determine the level of acceptance of mothers under five to innovation and to determine the effect of giving Moringa leaf innovation on increasing toddler weight. This type of research was quasi-experimental to determine the effectiveness of giving innovation to changes in toddler's weight, while to determine acceptability using organoleptic tests. The research was conducted from May to June 2022. The number of research subjects was 99 toddlers and mothers of toddlers. Data analysis to determine the level of acceptability used organoleptic tests, while to determine the effect of giving innovation after treatment used the Paired sample t-test. The results showed that the mother's assessment of the brownies, especially the color and aroma, quite liked it, while the texture and taste criteria liked and the assessment for the sponge rolls the criteria for liking the color, aroma and taste indicators, while the texture indicator the criteria really liked. The toddler's weight before giving the innovation was 8,7 kg and after the treatment the toddler's weight increased to 9,1 kg. The conclusion of the study is that the subject's acceptance of brownies, especially the texture and taste indicators, gets the criteria of liking and acceptance for the roll cake, the texture indicator gets the criteria of really liking it. There is an effect of giving Moringa leaf innovation on increasing toddler's weight.